Exploring the nature of stigmatising beliefs about depression and help-seeking: Implications for reducing stigma - Christensen Helen; Griffiths Kathleen M; Barney Lisa J; Jorm Anthony F (BMC, 2009)
Abstract Background In-depth and structured evaluation of the stigma associated with depression has been lacking. This study aimed to inform the design of interventions to reduce stigma by systematically investigating community perceptions of beliefs about depression according to theorised dimensional components of stigma. Methods Focus group discussions were held with a total of 23 adults with personal experience of depression. The discussions were taped, transcribed and thematically analysed. Results Participants typically reported experiencing considerable stigma, particularly that others believe depressed people are responsible for their own condition, are undesirable to be around, and may be a threat. Participants expressed particular concerns about help-seeking in the workplace and from mental health professionals. Conclusion Findings indicate that interventions to reduce the stigma of depression should target attributions of blame; reduce avoidance of depressed people; label depression as a 'health condition' rather than 'mental illness'; and improve responses of help-sources (i.e. via informing professionals of client fears).